Implementasi Pembelajaran Nilai-Nilai Pancasila Dalam Pendidikan Moral dan Etika Untuk Generasi Muda - Andika Adnan Tamami; Nayla Salsabila; Raras Noviana Putri; Rhyno Fairuz Melin; Rizqi Tsalats Fauzan; Subhan Alief Putra Firdaus; Yayang Furi Furnamasari (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2024)
The formation of a strong and responsible character, it is very important to instill the values of Pancasila in the moral and ethical education of the younger generation. The implementation of learning Pancasila values includes understanding and appreciation of the five precepts that form the basis of Indonesia's state ideology. This learning process involves interactive and contextual teaching methods, including discussions, simulations and relevant social activities. In addition, the importance of the educator's role in conveying these values in an effective and engaging manner is one of the keys to success. The main objective of this implementation is to develop attitudes and behaviors that reflect the values of Pancasila, such as tolerance, justice, humanity, unity, and democracy. Thus, the younger generation is expected to contribute positively to the life of society, nation and state, and face global challenges with strong principles.